Pengaruh Metode Pembelajaran Problem Solving Terhadap Motivasi Belajar Pendidikan Agama Kristen dan Budi Pekerti Siswa Kelas X SMA Negeri 1 Simanindo Tahun Pembelajaran 2022/2023 (International Forum of Researchers and Lecturers, 2023)
The aim of this research is to determine whether there is a positive and significant influence between the Problem Solving learning method on the motivation to learn Christian Religious Education and Characteristics of class X SMA Negeri 1 Simanindo students for the 2022/2023 academic year. The research method used is a quantitative descriptive inferential method. With a population of all class X SMA Negeri 1 Simanindo students of 155 people and a sample of 48 people was determined using random sampling techniques. The results of data analysis show that there is an influence of the Problem Solving learning method on the learning motivation of Christian Religious Education and Characteristics of class (=0.05,n=48) = 0.284. b) Testing a significant relationship obtained a value of tcount= 5.320 > ttable(=0.05,dk=n-2=46)= 2.021. 2) Test the effect: a) Test the regression equation, obtained the regression equation Ŷ =10.96+0.61X. b) Regression coefficient of determination test (r2) = 38.1%. 3) Test the hypothesis using the F test to obtain Fcount > Ftable=(=0.05, dk numerator k=23, dk denominator=n-2=48-2=46) namely 28.23 > 1.51. Thus Ha is accepted and H0 is rejected.